Development law of composite roof plate deformation and damage morphology and control countermeasures for trapezoidal roadway along gob - Yubo Li; Guohua Zhang; Zibo Li; Tao Qin; Gang Chen; Jiazhen Li (Scientific Reports)
Abstract To address the severe deformation and instability of the trapezoidal gob-side roadway’s composite roof plate. Using the 36# transport roadway in the left four working faces of Xinghua Coal Mine as the engineering background, the study integrates field testing, theoretical analysis, and numerical modeling. The study analyzes the deformation characteristics and damage factors of the trapezoidal roadway roof. It reveals the developmental morphology of roof deformation and damage patterns. The study proposes measures to “strengthen both sides of the roadway and reduce the extent of roof damage,” followed by identifying “the maximum sinking position of the roof plate and regulating its damage pattern” to control surrounding rock stability. Field measurements were conducted to verify the feasibility of these control measures. The results show that:① The maximum subsidence of the top plate of the trapezoidal roadway is located in the low gang position off the central axis of the roadway, i.e. 0.50l ~ 0.52l. As the rock girder’s inclination and section height increase, the maximum roof subsidence shifts toward the low gang. The overlying rock load, roof span width, and beam inclination positively correlate with roof deflection, while the beam’s elastic modulus and section height negatively correlate with it.② As the principal stress deflection angle shifts from 30° to 60°, the eccentric vault extends towards the gob area, transforming from a hump shape to a slanting roof. The damage range of the vault expands from 1.98 m to 4.42 m, and its offset from the central axis of the roadway grows from 0.92 m to 2.94 m.③ The combination form of the composite roof plate varies, with the eccentric vault taking a hump shape and positioned about 0.94 m from the roadway axis. The extent of damage to the eccentric vault follows this order: scheme 1 > scheme 3 > scheme 4 > scheme 2. At the junction between the soft and hard layers of the composite roof plate, an anomalous plastic zone forms. The hard layer develops a concave plastic area, while the plastic zone in the soft layer develops a convex form, creating a concave zone. ④Field measurements indicate a maximum separation of 17 mm in the composite roof plate, showing good overall integrity in the trapezoidal gob-side entry.